'Adopt an athlete for Rio 2016': the impact of austerity on the Greek elite sport system. Issue 1 (2nd January 2018) - Papadimitriou, Dimitra; Alexandris, Konstantinos
ABSTRACT: Drawing on the analysis of the experience of elite athletes in Greece during their 4-year preparation for competing in the 2016 Olympic Games, we report on the effects of the austerity measures on the country's elite sport system and policies. The data set for this study consisted of 16 semi-structured interviews of which 13 were conducted with Greek elite athletes participating in the 2016 Olympic Games and 3 were conducted with staff members of the Greek Olympic Committee supporting the Olympic delegation. The interview questions were based on the four pillars composing the throughput stage of the Sports Policy Factors Leading to International Sporting Success conceptual framework for analysing sports policy leading to international sporting success. The results clearly indicated that significant factors of the elite sport system were negatively influenced by the austerity measures in Greece. Because of the significant cuts in public spending, Olympic facilities were abandoned, highly qualified coaches became part-time employees, elite athletes were left with almost no opportunities to take part in international sport events and paramedical support for elite athletes was reduced drastically. The programme of the Greek Olympic Committee 'Adopt an athlete for Rio 2016' appeared as the only means for Greek elite athletes to make it to Rio de Janeiro, where they earned six Olympic medals. This study concluded that austerity measures have pronounced effects on elite sport systems, but not necessarily on achieving Olympic success.